Edukasi Personal Hygiene Pemeriksaan Candida sp. Pada Siswa SMPN 13 Samarinda - Raudah, Siti; Wahid, Rifky Saldi A. (Program Studi Teknologi Laboratorium Medis, ITKES Wiyata Husada Samarinda, 2022)
Personal hygiene is human self-care in order to maintain a healthy body. The maintenance of the cleanliness of each individual is very necessary for the comfort of the body, as well as for maintaining health. Candida sp. is a single-cell fungus, round to oval in shape, of all species found in humans, Candida albicans is one of the most pathogenic Candida species. Candida sp. grows as budding yeast cells and is oval (3-6 m in size) in culture or tissue. Fungi can cause quite severe diseases in humans, these diseases include candidiasis or candidosis, which is a fungal disease of the skin, nails, mucous membranes and internal organs caused by candida. Fungal infections are quite common in Indonesia because it is a tropical country with a hot and humid climate, especially if hygiene is not perfect. This community service aims to provide personal hygiene education and examination of Candida sp to students of SMPN 13 Samarinda.